DIALOGUE OR MONOLOGUE: A STUDY ON PUBLIC PARTICIPATION IN URBAN IMAGE COMMUNICATION BASED ON SOCIAL MEDIA (Proceedings of the World Conference on Media and Mass Communication, 2023)
The dialogue feature of social media has made it not only a vehicle for communicating the image of a city, but also the rising power of the public, opening new opportunities for the public to work with government agencies to promote the communication of a city's image. As the two main bodies of urban image communication, the communication between the public and government agencies through social media is strengthening. But does this active participation form a dialogue mechanism with government agencies and jointly promote the development of urban image communication, or is it just the public's monologue? Focusing on this issue, this study attempts to understand the impact of citizens' social media participation on the relationship between the subjects of urban image communication, and explores the mechanism for establishing a cooperative dialogue between the two subjects. This study mainly uses the qualitative research method of in-depth interview, combined with the observation method and using the city of Suzhou in Anhui Province as a case study. Based on interviews with public and government new media operators and managers in Suzhou and observations of their social media interactions, we found that the interactive dialogue between the public and government agencies is more convenient and in-depth than in the traditional media period, but no effective dialogue mechanism has been formed, public participation has not been fully valued by the government, and there is a problem of monologue. This study provides new ideas for the formation of a dialogue mechanism between the public and the government in city image communication, and explores the path to solve the monologue dilemma of public participation, to promote the improvement of the effectiveness of city image communication under communication participation and help urban development.
Keywords: Keywords: public participation, government agency, social media, dialogue mechanism, city image communication